2018
DOI: 10.3390/wevj9010008
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and Evaluation of Battery Packs with Different Numbers of Paralleled Cells

Abstract: To better evaluate the configuration of battery packs in electric vehicles (EV) in the early design phase, this paper proposes a mathematic model for the simulation of battery packs based on the elementwise calculations of matrices. This model is compatible with the different battery models and has a fast simulation speed. An experimental platform is built for the verification. Based on the proposed model and the statistic features of battery cells, the influence of the number of paralleled cells in a battery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…A circuit diagram of the used four switched synchronous DC/DC Buck-boost converter is shown in Figure 7 in which the battery cells are charged by the PV supply voltage V PV [28,29]. Four peculiar MOSFET switches (S 1~S4 ) are tangled into the DC/DC converter to standardize the energy transference of battery arrangements (V nBat ).…”
Section: Dc/dc Buck-boost Convertermentioning
confidence: 99%
“…A circuit diagram of the used four switched synchronous DC/DC Buck-boost converter is shown in Figure 7 in which the battery cells are charged by the PV supply voltage V PV [28,29]. Four peculiar MOSFET switches (S 1~S4 ) are tangled into the DC/DC converter to standardize the energy transference of battery arrangements (V nBat ).…”
Section: Dc/dc Buck-boost Convertermentioning
confidence: 99%
“…However, the work, which has been done in this field so far, does not include a comprehensive analysis of the costs and losses associated with different configurations of the CHB inverter, e.g., the number of levels, selection of switches, etc. There are setups described with only three levels [21] and up to eleven [14,22], twenty-one [23,24] or even twenty-three levels [25,26] with a big majority focusing on seven level CHB inverters [8,[27][28][29][30][31][32]. Only one publication was found comparing different configurations, but only with regards to efficiency and without any cost consideration [33].…”
Section: Of 19mentioning
confidence: 99%
“…Baumhoefer et al [7] have shown that the cells with different initial capacities in a battery pack age differently over time, and the variation of capacities increases. An explanation for this is that putting the same load on weaker cells would degrade them faster as compared to the healthier cells [8]. These inconsistencies may limit the performance of a battery pack and reduce its lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…In order to accurately predict the SoP of a battery system including parallel-connected units, comprehensive modeling and analysis of the entire battery system's operation, especially the dynamic parallel current distribution, are required. Parallel operation of battery cells has been modeled for performance evaluation [16]- [19] as well as sensitivity analysis to heterogeneous cell resistance [16], [17], [19]- [21], charge capacity [16], [17], [19], [21]- [24], number of parallel cells [18], [23], and system configuration [16]. However, to the best of our knowledge, the complete battery system modeling considering time-varying parallel current distribution has not been applied to the battery system SoP prediction due to significantly increased complexity in system modeling and algorithm design as compared to those commonly used cell-SoP-based methods.…”
Section: Introductionmentioning
confidence: 99%